Spaciousness of the Matoš’s Voice - Pinter, Kornelija (Poznańskie Studia Slawistyczne, 2014)
The voice connections observed within the A.G. Matos’s poetry establish the poem’s space/ the poem’s body. The grammar of the speech, grammar of the body and grammar of the poem are connected with the same category – the spaciousness. The insight of the voice metaphors highlights the relationship between the voice, body and space stressing the relationship as a condition of the poem’s voice and body existence.